Impact of Narrative Therapy on Identity Reconstruction and Motivation in Clients with Acquired Brain Injury - Turan, Selva; Rahman, Farhana; Dimitrov, Ivan (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to evaluate the effectiveness of narrative therapy in enhancing identity reconstruction and motivation among individuals with acquired brain injury (ABI). A randomized controlled trial was conducted involving 30 participants with ABI recruited from rehabilitation centers in Bangladesh. Participants were randomly assigned to either an intervention group (n = 15), which received nine weekly sessions of narrative therapy, or a control group (n = 15), which received standard care. Data were collected at three time points: pre-test, post-test, and five-month follow-up. Identity reconstruction was measured using the Self-Concept and Identity Measure (SCIM), and motivation was assessed using the Motivation for Traumatic Brain Injury Rehabilitation Questionnaire (MOT-Q). Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests with SPSS-27. The results showed a significant improvement in identity reconstruction and motivation scores in the intervention group compared to the control group across time. The intervention group’s identity scores increased from a pre-test mean of 71.43 (SD = 6.28) to 82.67 (SD = 5.19) at post-test and were sustained at follow-up (M = 81.74, SD = 5.44). Similarly, motivation scores rose from 98.21 (SD = 7.03) to 110.36 (SD = 6.45), remaining stable at follow-up (M = 109.87, SD = 6.33). Repeated measures ANOVA confirmed significant time × group interactions for both variables (p < .001), and Bonferroni post-hoc tests indicated that the observed improvements were statistically significant and maintained over time. Narrative therapy proved effective in promoting identity reconstruction and increasing motivation in individuals with ABI, with sustained benefits observed at five-month follow-up. These findings highlight the therapeutic value of narrative-based interventions in neurorehabilitation settings.